Corporate strategies for Philippine Telegraph & Telephone Corporation - Go, Susan C. (Animo Repository, 1997)
With the recent liberalized environment of the telecommunication industry, Philippine Telegraph and Telephone Corporation (PT&T) found itself in a situation filled with opportunities and threats. In order to stay competitive, the company realized the need to refocus its resources in the high growth segment of the industry and continuously provide value-added in its traditional services. It has strengthened its strategic and financial position through an alliance with telecommunication stalwarts, Korea Telecoms and A2 Telecommunications which together with Telectronics Systems, Inc. forms the powerful holding company called Republic Telecommunications, Inc. or RETELCOM. With its extensive digital terrestrial backbone, PT&T hopes to play a significant role the countrys telecommunication industry.